2005
DOI: 10.1021/mp049894a
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Boron Compounds in an Animal Model of Human Undifferentiated Thyroid Cancer for Boron Neutron Capture Therapy

Abstract: Undifferentiated thyroid carcinoma (UTC) is a rapidly growing, highly invasive malignant tumor that currently lacks any effective treatment. Boron neutron capture therapy (BNCT) has been investigated recently for some types of tumors including glioblastoma multiforme and malignant melanoma. In previous studies we have shown the selective uptake of p-boronophenylalanine (BPA) by undifferentiated thyroid cancer cells in vitro and in vivo, as well as the histologic cure of 50% of the nude mice transplanted with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…from 1-7 days before BPA and the boron uptake was measured 60 min after BPA administration. We observed that the combination of 5 days after BOPP and 60 min after BPA the boron uptake was 45 ppm, doubling the results obtained with BPA alone (10).…”
Section: Uptake Of a Boronated Porphyrin (Bopp)mentioning
confidence: 40%
“…from 1-7 days before BPA and the boron uptake was measured 60 min after BPA administration. We observed that the combination of 5 days after BOPP and 60 min after BPA the boron uptake was 45 ppm, doubling the results obtained with BPA alone (10).…”
Section: Uptake Of a Boronated Porphyrin (Bopp)mentioning
confidence: 40%
“…Intensive research has led to the design and study of many porphyrin conjugates with carborane units, such as porphyrins substituted in their meso-positions 292,343-359 and on the porphyrin core itself, 360 or protoporphyrin IX derivatives such as BOPP (the tetrakis-carborane carboxylate ester of 2,4-bis-(1,2-dihydroxyethyl)deuteroporphyrin IX) (Figures 36-38). [361][362][363][364][365][366][367][368] An interesting result was obtained by Perona et al using BOPP as a radiosensitizer. 369 They found that cancer cells (WRO, follicular cancer cell line) displayed approximately three times higher sensitivity for BNCT than normal control cells.…”
Section: Porphyrin and Expanded Porphyrin Applications For Combinementioning
confidence: 99%
“…Although these drugs are safe, they can deliver to the tumor only a limited amount of boron, and therefore other new boron compounds, such as boronated porphyrins, are being analyzed. Tetrakiscarborane carboxylate ester of 2,4-bis-(a,b-dihydroxyethyl)-deutero-porphyrin IX (BOPP) has been shown to be a good boron carrier in different animal models (4,5). Recently BNCT has also been applied to the treatment of liver metastases of colon cancer.…”
Section: Introductionmentioning
confidence: 99%